2006
DOI: 10.1007/s10995-005-0056-9
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Social Networks and Support in Postpartum Women's Depression: A Multiethnic Urban Sample

Abstract: Both social support and social networks were statistically significant and independently related to depressive symptomatology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
87
0
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(102 citation statements)
references
References 33 publications
8
87
0
7
Order By: Relevance
“…O referido resultado corrobora conclusões abordadas em outros estudos (Baptista et al, 2006;Hopkins & Campbell, 2008;Surkan, Peterson, Hughes & Gottlieb, 2006). Na pesquisa realizada por Baptista et al (2006), foi encontrada uma relação negativa entre os sintomas depressivos e a percepção de suporte social.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…O referido resultado corrobora conclusões abordadas em outros estudos (Baptista et al, 2006;Hopkins & Campbell, 2008;Surkan, Peterson, Hughes & Gottlieb, 2006). Na pesquisa realizada por Baptista et al (2006), foi encontrada uma relação negativa entre os sintomas depressivos e a percepção de suporte social.…”
Section: Discussionunclassified
“…Corroborando os resultados encontrados neste estudo, a pesquisa realizada em centros de saúde da cidade de Northeastern com 415 mães de recém-nascidos constatou que, no que diz respeito à relação entre suporte social e sintomas depressivos, havia uma associação negativa entre esses aspectos (Surkan, Peterson, Hughes & Gottlieb, 2006). Todavia, salienta-se que, além do escore total de apoio social, foram investigadas também as relações entre as dimensões de apoio e a sintomatologia depressiva.…”
Section: Discussionunclassified
“…The few studies that have focused on mothers of color concluded their rates of postpartum depression to be higher than among White mothers (CDC, 2008;Surkan, Peterson, Hughes, & Gottlieb, 2006). Yet, social workers employed in maternal and child health settings looking to advance their skills in working with mothers with postpartum depression from non-White backgrounds have a limited body of social work literature to draw upon.…”
Section: The Varying Rates Of Postpartum Depressionmentioning
confidence: 99%
“…Surkan et al examined the relationship of social support and social networks to symptoms of depression in a multiethnic sample of early postpartum women (Surkan et al, 2006). Univariate statistics assessed the relationship between Center for Epidemiologic Studies of Depression Scale (CES-D score) and each of the independent variables.…”
Section: Relation To Social Supportsmentioning
confidence: 99%